GEOGRAPHY OF GREAT BRITAIN - Ahmedova Mahliyo; Soyibjonova Feruza; Olimjonova Sevinch (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Great Britain is an island in the North Atlantic Ocean off the north- west coast of continental Europe. With an area of 209,331 km2 (80,823 sq mi), it is the largest of the British Isles, the largest European island and the ninth-largest island in the world. It is dominated by a maritime climate with narrow temperature differences between seasons. The island of Ireland, with an area 40 per cent that of Great Britain, is to the west—these islands, along with over 1,000 smaller surrounding islands and named substantial rocks, form the British Isles archipelago.